2018
DOI: 10.1002/marc.201800073
|View full text |Cite
|
Sign up to set email alerts
|

Centrosymmetric Thiophenemethyleneoxindole‐Based Donor–Acceptor Copolymers for Organic Field‐Effect Transistors

Abstract: Two novel, donor-acceptor-type π-conjugated polymers (P1 and P2) with 3'-(thieno[3,2-b]thiophene-2,5-diylbis(methan-1-yl-1-ylidene))bis-(indolin-2-one) (ITTI) as the acceptor and thiophene/bithiophene as the donor are designed and synthesized by palladium-catalyzed Stille coupling. The optical and electrochemical properties of these polymers are characterized and further implemented into organic field-effect transistors (OFET). Both polymers exhibit excellent thermal stability, broad UV-vis absorption, and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In 2018, Zhang et al (2017) reported that introducing hydrogen bonding between the amide and carbonyl into the polymer not only result in polymer self-assembly, but also increases the electron mobility by a factor of 40 compared to its precursor polymer ( Figure 1F ). Recently, Deng et al (2018) introduced S and F atoms to adjust the polymer backbone and obtained a polymer with hole mobility up to 0.65 cm 2 V −1 s −1 . Zhang et al then reported that the main chain coplanarity of polymer semiconductors is more essential than the sole extension of π-conjugation (especially perpendicularly to polymer main chains) after investigating two benzo/naphtodifuranone-based polymers ( Figure 1G ) ( Li et al, 2021 ).…”
Section: Organic Field Effect Transistormentioning
confidence: 99%
“…In 2018, Zhang et al (2017) reported that introducing hydrogen bonding between the amide and carbonyl into the polymer not only result in polymer self-assembly, but also increases the electron mobility by a factor of 40 compared to its precursor polymer ( Figure 1F ). Recently, Deng et al (2018) introduced S and F atoms to adjust the polymer backbone and obtained a polymer with hole mobility up to 0.65 cm 2 V −1 s −1 . Zhang et al then reported that the main chain coplanarity of polymer semiconductors is more essential than the sole extension of π-conjugation (especially perpendicularly to polymer main chains) after investigating two benzo/naphtodifuranone-based polymers ( Figure 1G ) ( Li et al, 2021 ).…”
Section: Organic Field Effect Transistormentioning
confidence: 99%
“…[ 11–14 ] Specifically, the backbone structures of CPs, not only has a crucial effect on the intramolecular π‐orbital overlap and delocalization, but also play an important role for enhancing the inter‐(macro)molecular interactions via π–π stacking. [ 15,16 ] Therefore, numerous strategies of tailoring the backbone structures of CPs such as quinoidalization, ladderization, incorporation of non‐covalent interactions, or simply π‐extension of the building blocks within main chains have been applied for the ultimate purpose of delivering high performances in different organic electronic devices. [ 17–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory (DFT) calculations were carried out for the monomers and two repeating units of the polymers, employing a B3LYP/6-31G* basis set with alkyl side chains simplified as a methyl group. , The optimized geometries of the monomers and the polymers are displayed in Figure S14 and Figure S15, respectively, and related dihedral angles data are summarized in Table S2. The DPP-H was a planar structure, and the DPP-B was slightly out of co-planarity because of coordination with boron difluorides.…”
Section: Resultsmentioning
confidence: 99%